Emerging sustainability themes in the hospitality sector: A bibliometric analysis - Sofía Blanco-Moreno; Mine Aydemir-Dev; Carmen R. Santos; Nuran Bayram-Arlı (European Research on Management and Business Economics)
This paper presents a bibliometric analysis of 837 publications on sustainability in the hospitality sector, specifically in hotels and restaurants, covering the period from 2010 to 2023. The study assesses the principal research themes and applied methodologies. The study examined three periods: pre-COVID-19, COVID-19, and post-COVID-19. The authors conducted a bibliometric study of journals included in the Web of Science related to the field over the past 14 years. The analysis was carried out through comprehensive indexing of articles and the application of the bibliometric research tool SciMAT. Specifically, a productivity map and a science map are presented, inferring potential lines of research. The results reveal key trends in sustainability research, highlighting predominant themes such as ‘behaviour’, ‘consumers’, ‘business big data’, ‘marketing’, ‘perceived value’, ‘CSR’, ‘local food’, ‘over-tourism’ and ‘SDG’, while a deeper understanding of ‘sustainable communication’, ‘environmental marketing strategy’, ‘green spaces’ and ‘consumer preferences’ were lacking. Addressing these issues could motivate the development of a more positive attitude toward sustainable travel. In terms of methodologies, there was a noticeable lack of data mining, neuromarketing, and co-word analyses. This paper provides clarity on new and necessary approaches and business models to provide resilience to the sector and to involve clients in the travelling experience.